Model Pure Community-smart Cities (PCSC) Components Assessment in Lembah Klang, Malaysia from Society 5.0 to Madani Society - Abdul Malek, Jalaluddin; Adawiyah Baharudin, Rabeah (KnE Social Sciences, 2024)
Pure community is one of the elements that must be present to create a holistic smart city that is not only focused on economic development. This study aims to measure the level of development of the pure community in the cities of the Klang Valley, Malaysia. The research was conducted at the Klang Valley, Peninsular Malaysia. This study uses cluster sampling to select the respondents. Stratified sampling is a technique used for dividing the population into specific characteristics, and then using simple random sampling, samples are taken from each population. Overall, the level of pure community in Malaysia’s Klang Valley shows that they have a high value of good citizens. Despite this, it is crucial to put a guideline that allows the involvement of urban citizens to carry out mutual responsibilities in the location of their residence to be more organized. The government should be able to create an appropriate task force in the housing area that involves shared responsibility between the city’s residents. Keywords: smart city development, pure community, Model PCSC